Формування середньої маси плодів яблуні за дії мінеральних добрив - Машківський, Віктор; Іванова, Ірина Євгенівна; Кривонос, Ірина Анатоліївна; Mashkivskyi, Viktor; Ivanova, Iryna; Kryvonos, Iryna (Запоріжжя : ТДАТУ, 2024)
UA: Яблуня серед плодових культур в Україні є культурою-лідером по займаній площі насаджень, показникам врожаю та затребуваності плодів у свіжому вигляді на ринку країни та за її межами. Це обумовлено унікальною адаптивною спроможністю культури, розмаїттям її господарсько цінних ознак, традиціями населення, дієтичними та лікувально-профілактичними якостями плодів. Відповідно до Державної програми відродження галузі садівництва заплановано збільшити площі інтенсивних садів за рахунок насичення їх сортами, які забезпечують вирощування конкурентоспроможної продукції для споживача. Інтенсифікація вирощування культури, яка базується на підборі сортів, підщеп, оптимізації агротехнічних заходів й, зокрема, удобрення в конкретних грунтово-кліматичних умовах є актуальним питанням сьогодення. Метою досліджень було – розробити систему удобрення дослідженого сортименту яблуні, яка б забезпечила оптимальні показники якості плодів досліджуваної культури. В ході досліджень було виявлено формування маси плодів в залежності від рівнів удобрення. Досліджувані сорти відрізнялися розмірами. Найбільша їх середня маса відзначена у сорті «Голден Делішес» (154г) і найменша у – «Флоріна» (105г). Застосування мінеральних добрив сприяло збільшенню маси яблук сортів «Айдаред» та «Голден Делішес». EN: Among fruit crops in Ukraine, apple is the leading crop in terms of planted area, yield and demand for fresh fruit in the country and abroad. This is due to the unique adaptive capacity of the crop, the diversity of its economically valuable traits, the traditions of the population, and the dietary and therapeutic and prophylactic qualities of the fruit. Fruits of pome and stone fruit crops contain a complex of vitamins, easily digestible carbohydrates, organic acids and trace elements. The latter are an essential condition for the full functioning of the human body. According to the State Programme for the Revival of the Horticulture Sector, it is planned to increase the area of intensive orchards by saturating them with varieties that ensure the cultivation of competitive products for consumers. The intensification of crop cultivation based on the selection of varieties, rootstocks, optimization of agronomic measures and, in particular, fertilization in specific soil and climatic conditions is a pressing issue today. The aim of the research was to develop a fertilization system for the studied apple variety that would ensure optimal fruit quality indicators of the crop under study. To achieve the goal of the research, the following task was performed: to study the formation of fruit weight of apples of the studied varieties under the influence of different doses and ratios of mineral fertilizers applied to the soil. The research revealed the formation of fruit weight depending on fertilization levels. The studied varieties differed in size. The highest average weight was observed in the «Holden Delishes» variety (154g) and the lowest in «Florina» (105g). The use of mineral fertilizers contributed to an increase in the weight of apples of «Aidared» and «Holden Delishes» varieties.
Formation of the average weight of apple fruit under the influence of mineral fertilisers
Keywords: сорти плодів яблук; показники якості; рівні удобрення; дисперсійний аналіз; фактор; apple fruit varieties; quality indicators; fertilizer levels; analysis of variance; factor